Kepemimpinan Transformasional Kepala Madrasah dalam Meningkatkan Kinerja Guru di Madrasah Ibtidaiyah Sultan Agung Karangduwur, Ayah, Kebumen - Ngaziz Ngaziz (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2019)
This research is based on the problem of unsatisfactory teacher performance. In this regard, this study aims to determine the transformational leadership of madrasa heads in improving teacher performance at MI Sultan Agung Karangduwur, Ayah District, Kebumen Regency. This research is a qualitative research. Data collection used interviews, observation, and documentation, and the validity of the data used triangulation, and data analysis techniques included data collection, data reduction, data presentation, and drawing conclusions. This study resulted in the following conclusions. (1) Head of MI Sultan Agung Karangduwur, Ayah, Kebumen owns and implements Idealized influence. The behavior of the madrasa head can be used as an example for madrasa residents. In his daily life, the principal can provide motivation and self-confidence to his subordinates. The principal of the madrasa is able to give empathy to his subordinates. (2) Head of MI Sultan Agung Karangduwur, Ayah, Kebumen owns and implements Inspirational influence. The behavior of the madrasa head is able to motivate and inspire his subordinates to continue to bring progress to the madrasa. The principal of the madrasa always gives new job challenges. The madrasa head is able to be a pioneer of goodness for madrasa residents. (3) Head of MI Sultan Agung Karangduwur, Father, Kebumen owns and implements Intellectual stimulation. The behavior of the madrasa head is based on science, which is able to carry out innovations to improve the quality of madrasas. The principal of the madrasa always follows changes by behaving productively. The madrasa head is able to explore new ideas and creative solutions from his subordinates. (4) Head of MI Sultan Agung Karangduwur, Father, Kebumen owns and carries out Individualized consideration. The madrasa head always identifies the needs of his subordinates and recognizes the abilities of his subordinates. The principal of the madrasa evokes enthusiasm for learning and provides opportunities for his subordinates to develop their abilities. The madrasa head also listens to subordinates' complaints and delegates some of his authority to his subordinates.